Why Participation Matters: Communal Drinking Water Management in Bolivia and Ecuador. (March 2014) - Armijos, Maria Teresa; Walnycki, Anna Maria
Abstract In the past 30 years, Drinking Water Users' Associations (DWUAs) have emerged in peri‐urban and rural areas in Bolivia and Ecuador where public utilities do not operate. While recognising the challenges to service provision and the problematic around the role of the state that exists in both countries, this article seeks to understand why and how local participation in drinking water systems has been so important for the formation of newly formed peri‐urban and rural communities in both Andean nations. It argues that through participation in collective (communal) activities and decision‐making, communities are constructed. This article will highlight, through our own experiences, why it became so important for us as researchers to participate in communal water management activities during fieldwork.